Analisis Balanced Scorecard sebagai Alat Pengukuran Kinerja Perusahaan di Bank BJB KCP Gatot Subroto - Nabilah Novitha Rani; Mario Aldo T. Abidin; Efson Thrismono (Ma'soem University, 2022)
Based on observations, that the background of this research is that there are several companies measuring their performance still using traditional methods, therefore the author will measure performance with modern methods by applying the Balanced Scorecard method as a performance measurement tool. This study aims to determine how to measure performance using the Balanced Scorecard method with four perspectives, namely: financial perspective, customer perspective, internal business process perspective and learning and growth perspective. The object of research in this report is to measure the company's performance using the balanced scorecard. This type of research is descriptive qualitative with primary and secondary data types using data collection techniques in the form of observation, interviews, literature study and documentation. While the data collection techniques from these four perspectives used observation and interview techniques. The results of the analysis show that performance measurement from a financial perspective provides an indicator of 0.635 which is declared good, measured using asset growth, increased profits, increased financing and asset optimization. The result of measuring the performance of the customer perspective is worth 0.75 which is declared good, measured using customer retention, customer acquisition and customer satisfaction. The results of the measurement of the performance of the internal business process perspective get a score of 1 which means good, measured using the operation process, the innovation process and after-sales service. The results of measuring the performance of growth and learning perspectives get a score of 0.5 which means enough, measured using employee retention, employee turnover, employee productivity and employee absenteeism.